SOFTWARE FOR VIJING AND VIDEO MAPPING: FEATURES AND ARTISTIC OPPORTUNITIES - Габрель, Т. М. (Art and Design, 2023)
Goal: to consider the main graphics packages for VJing and video mapping and to conduct a comparative analysis of the main programs with the help of which video artists create visual effects to music in real time, creating a "video mix" – a fundamentally new work formed mainly from pre-prepared video fragments. Methodology. The research used the empirical method, as well as the theoretical method of comparative analysis. The results. The main data on the programs for weeding were analyzed and systematized, which made it possible to track the key information characterizing the specialized software and to make a choice in favor of one or another program, taking into account the specific task and conditions of activity. For the purpose of the study, a table was compiled that reflects the characteristics of the programs, such as: the operating system, the year the program was released, the number of active users, the number of channels for mixing, the ability to create generative graphics in the program, support for certain protocols and modules, as well as the cost of the software and having a teaching license. Scientific novelty. A comparative analysis of widget and video mapping software was performed and information about them was systematized. It has been established which programs are the flagships and favorites in the software market, as well as which programs have significant prospects in the future. Practical significance. A comparativeeview of widget programs helps to highlight among them the most promising for development, which are actively supported by developers, as well as those that are stagnant. An overview of the main graphic packages for VJegging, a comparison of their capabilities and recommendations for choosing the optimal software are useful for performing artistic activities for VJejs and media artists.